Case report: An invasive and giant hemolymphangioma of the pancreas in a young man - Wang, Pin; Wang, Mancai; Liu, Yongyong (Frontiers in Oncology, 2025)
Hemolymphangioma is a rare benign tumor, with only 12 reported cases in the pancreas as of May 2024. We present an invasive and giant hemolymphangioma of the pancreas in a young man who experienced abdominal pain and left epigastric distension for approximately 10 days. Imaging studies revealed a large cystic tumor located in the body and tail of the pancreas, which was compressing the partial lesser curvature of the stomach and spleen, displaying a “beaver tail” liver appearance on computed tomography scans. After surgery, he was diagnosed with hemolymphangioma of the pancreas, and there were no signs of recurrence upon follow-up. We conclude that diagnosing hemolymphangioma of the pancreas can be challenging. Whenever possible, radical surgical resection should be performed, and long-term follow-up is essential.